Povezanost telesne aktivnosti študentov s študijskim uspehom - Lipošek, Silvester (Šport (Ljubljana), 2019)
It is common knowledge that regular physical activity of children, adolescents and adults positively influences general health. Regular and appropriate physical activity, its adequate intensity and duration, increases body fitness. General fitness and physical activity have proven to have a positive effect on perception and concentration. For a long time research found no significant link between physical activity and academic achievement, especially since focus with physical activity research was on cardio-vascular fitness (durability). When scientists began to explore other facts, they observed positive correlation between some dimensions of psychomotor abilities, cognitive abilities and academic achievements; namely, psychomotor skills and cognitive function have many common neurological mechanisms. Improvements in brain performance (increased blood circulation in the brain, increased levels of hormone improved by intake of nutrients, and increased vigilance) are associated with regular exercise.
Keywords: academic success; physical activity; students; študenti; telesna aktivnost; učni uspeh